1998
DOI: 10.1021/jp980969y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solvent Vapor Annealing on the Morphology and Photophysics of Molecular Semiconductor Thin Films

Abstract: The effect of solvent vapor annealing on the fluorescence properties and morphology of titanyl phthalocyanine/ perylene phenethylimide thin-film molecular semiconductor bilayers (TiOPc/PPEI) is investigated. A combination of atomic force microscopy (AFM) and near-field scanning optical microscopy (NSOM) is used in conjunction with bulk absorption and fluorescence measurements to correlate the morphological and photophysical properties of these bilayer systems. AFM data show that treatment of the vacuum-deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 39 publications
3
117
0
Order By: Relevance
“…Phthalocyanine and perylene tetracarboxylic acid (PTCD) materials are being tested in thin film devices as thin film molecular semiconductor bilayers [1] or for forming organic photovoltaic cells [2]. Several templates for device manufacture have been presented throughout the past decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phthalocyanine and perylene tetracarboxylic acid (PTCD) materials are being tested in thin film devices as thin film molecular semiconductor bilayers [1] or for forming organic photovoltaic cells [2]. Several templates for device manufacture have been presented throughout the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Hiramoto et al [5] reported the first threelayered organic solar cell with a photoactive interlayer of co-deposited metal-free phthalocyanine and a perylene tetracarboxylic derivative (Me-PTC). More recently, characterization of molecular thin films of perylene and phthalocyanine derivatives has been the main focus of research [1,[6][7][8][9][10]. Here we present the first study of codeposited MPc/PTCD mixed films using the methods of surface-enhanced vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that vapors from organic solvents would promote the crystalline transformation similar to methods used in materials research [40,41]. To test this, five polar solvents with varying CHCA solubility were evaluated for suitability for VIC and downstream SAMDI MS (Table S1).…”
Section: Vapor-sorption Induced Co-crystallization (Vic)mentioning
confidence: 99%
“…From an application perspective, we employ here a solventvapor treatment or "solvent annealing", [11][12][13][14] starting from a spin-coated poly(3-butylthiophene) (P3BT) film, to carry out the transformation of regioregular P3BT backbones from parallel to perpendicular orientation with respect to the substrate, together with the crystallographic transition from typical Form I to Form II. As illustrated by the wide-angle X-ray diffraction (WAXD) pattern shown in Figure 1, the reflection peak from the (100) Miller plane of Form I, which is around 2h = 7.2°(d-spacing 12.3 Å) in a WAXD profile, gradually disappears upon exposure to carbon disulfide vapor, accompanied by the appearance of the (100) reflection of Form II at 2h ≈ 9.2°(d-spacing 9.6 Å).…”
mentioning
confidence: 99%